The role of body image psychological flexibility on the treatment of eating disorders in a residential facility. (December 2016) - Bluett, E.J.; Lee, E.B.; Simone, M.; Lockhart, G.; Twohig, M.P.; Lensegrav-Benson, Tera; Quakenbush-Roberts, Benita
Abstract: Objective: The purpose of this study was to test whether pre-treatment levels of psychological flexibility would longitudinally predict quality of life and eating disorder risk in patients at a residential treatment facility for eating disorders. Method: Data on body image psychological flexibility, quality of life, and eating disorder risk were collected from 63 adolescent and 50 adult, female, residential patients (N = 113) diagnosed with an eating disorder. These same measures were again collected at post-treatment. Sequential multiple regression analyses were performed to test whether pre-treatment levels of psychological flexibility longitudinally predicted quality of life and eating disorder risk after controlling for age and baseline effects. Results: Pre-treatment psychological flexibility significantly predicted post-treatment quality of life with approximately 19% of the variation being attributable to age and pre-treatment psychological flexibility. Pre-treatment psychological flexibility also significantly predicted post-treatment eating disorder risk with nearly 30% of the variation attributed to age and pre-treatment psychological flexibility. Discussion: This study suggests that levels of psychological flexibility upon entering treatment for an eating disorder longitudinally predict eating disorder outcome and quality of life. Highlights: Role of psychological flexibility in eating disorder population knowledge Measurement of psychological flexibility in eating disorder population knowledge Body image psychological flexibility predicted post-treatment quality of life Body image psychological flexibility predicted post-treatment eating disorder risk